Analysis of Factors Which Cause Gen Z Employees to Choose the Profession as Zakat Amil In Baitul Maal Muamalat - Kamil, Musthafa; Sabariah, Etika; Hartini, Dorit; Handayani, Miranti; Syamsudin, Syamsudin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the factors that cause Generation Z employees to choose the profession of amil zakat at Baitulmaal Muamalaat using Abraham Maslow's need theory framework. This study uses a quantitative, non-statistical approach to gain a deeper understanding of the choice of this profession. The research method used was a survey involving Generation Z employees at Baitulmaal Muamalaat. This survey was designed with structured questions related to the factors that influence the choice of profession as amil zakat based on Maslow's theory of needs. Participants were asked to rate the importance of each factor and provide further explanation about their motivation. The data collected from the survey were analyzed qualitatively by identifying common themes that emerged about the motivational factors influencing the choice of this profession. This analysis provides an in-depth understanding of the factors that motivate Generation Z employees to choose the profession of amil zakat. This research contributes to understanding the choice of profession as amil zakat by Generation Z employees at Baitulmaal Muamalaat based on Maslow's theory of needs. Although using a quantitative, non-statistical approach, this research provides valuable insights into their motivation and the factors influencing their decisions.